ASSESMENT MODEL OF NAVAL WARSHIP (KRI) READINESS TO SUPPORT MAIN TASK OF THE NAVY - Prasetia, Heru; Wirjodirjo, Budisantoso; Hartoko, Priyadi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
KRI is a representation of the strength and ability of the Indonesian Navy in maintaining state sovereignty in the maritime jurisdictional area. The complexity of the threat in the area of operation will determine the amount, type and level of readiness of the KRI that will carry out the operation. Therefore, information on the level of readiness of the KRI